Life cycle analysis (lca) of non-structural partition wall systems: a comparison between gypsum plasterboard panels, masonry bricks, and papercrete blocks (2014)
Even though the main focus of sustainable developments in building projects has been operative-phase energy expenditure because of its direct impact in operational costs, embodied energy and its associated environmental impacts have gained importance over the last few years due to the relevance given to construction materials by green building accreditation systems. Rating systems for buildings such as USGBC¿s LEED and UK-BRE¿s BREEAM award the use of regional, certified, rapidly renewable materials with recycled content as well as its reuse. This paper considers three types of non-structural partition wall system using Life Cycle Assessment (LCA) techniques: drywall panels, masonry bricks and papercrete blocks.